Evaluation of Different Materials used in Prosthetic of Dental Implants: A Comparitive Study - Md Miftah ur Rahman; Rupasree Gundala; Kavita Gupta; Diptesh S. Rami; Nilesh Bhanawat; Harisha Dewan; Vilas Patel; Sirisha Kommuri (Wolters Kluwer Medknow Publications, 2024)
Background: Implant-supported prostheses have become a cornerstone of restorative dentistry, offering patients an effective solution for missing teeth. However, the choice of material for these prostheses can significantly impact their maintenance requirements and long-term success. Methods: Patient records of individuals who received implant-supported prostheses over a 2-year period were reviewed. Data on maintenance interventions, including adjustments, repairs, and replacements were collected and analyzed for metal alloys, ceramics, and composites. Results: Metal alloys exhibited slightly higher average numbers of adjustments compared to ceramics and composites. Ceramics required a higher mean number of repairs and replacements compared to other materials. Statistical analysis revealed significant differences in adjustment frequency between metal alloys and ceramics (P = 0.047), but no significant differences were observed for repairs or replacements. Conclusion: The outcomes imply that material choice plays a significant role in the maintenance requirements of implant dental prostheses. While metal alloys may require more frequent adjustments, ceramics and composites may necessitate more repairs and replacements over time. Clinicians should consider these factors when selecting materials for implant prostheses and develop tailored maintenance protocols to optimize treatment outcomes.